Delving Into the Interaction Between Exercise and Diabetes on Methylation of the FKBP5 Gene - Teng-Chi Yang; Jen Pi Tsai; Honda Hsu; Yen-Chung Chen; Yi-Chia Liaw; Shu Yi Hsu; Hao Jan Yang; Yung-Po Liaw (Journal of Diabetes Research)
Conclusion: This study demonstrates that the effects of exercise on FKBP5 methylation are site-specific and influenced by diabetes status. Exercise reduces methylation at cg22363520 in nondiabetics and at cg00862770 in diabetics, indicating its role in modulating epigenetic regulation of stress and metabolic pathways. These findings underscore the interplay between exercise, diabetes, and FKBP5 methylation, with potential implications for improving mental health and metabolic outcomes.